1999
DOI: 10.1093/ndt/14.7.1732
|View full text |Cite
|
Sign up to set email alerts
|

A modified quantitative subjective global assessment of nutrition for dialysis patients

Abstract: We conclude that our invented malnutrition score, which can be performed in minutes, reliably assesses the nutritional status of haemodialysis patients. We suggest that our malnutrition score may be superior to the SGA. More comparative and longitudinal studies are needed to confirm the validity of this scoring system in nutritional evaluation of dialysis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
212
0
20

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(243 citation statements)
references
References 7 publications
6
212
0
20
Order By: Relevance
“…6 In addition to SGA, the following are routinely assessed: nutrient intake, mainly by use of the three-day food recording or by use of 24-hour food recall; muscle and fat mass reserve by use of anthropometry or bioelectrical impedance; and biochemical Assessment of methods to identify protein-energy wasting in patients on hemodialysis markers by use of plasma albumin. [7][8][9] Renowned researchers in the area believe that it is necessary to jointly apply several parameters to properly assess the nutritional status of that population, to overcome the limitations of each of such methods when used in isolation. Despite all effort to establish a precise nutritional diagnosis, the normalization of nutritional parameters to be applied to patients with CKD still lacked.…”
Section: Introductionmentioning
confidence: 99%
“…6 In addition to SGA, the following are routinely assessed: nutrient intake, mainly by use of the three-day food recording or by use of 24-hour food recall; muscle and fat mass reserve by use of anthropometry or bioelectrical impedance; and biochemical Assessment of methods to identify protein-energy wasting in patients on hemodialysis markers by use of plasma albumin. [7][8][9] Renowned researchers in the area believe that it is necessary to jointly apply several parameters to properly assess the nutritional status of that population, to overcome the limitations of each of such methods when used in isolation. Despite all effort to establish a precise nutritional diagnosis, the normalization of nutritional parameters to be applied to patients with CKD still lacked.…”
Section: Introductionmentioning
confidence: 99%
“…27 Several studies have reported that anthropometric measurements and serum albumin levels decrease in parallel with malnutrition. 12,28 This suggests that malnutrition reduces the TSF, MAC, and MAMC, as well as serum albumin levels and lymphocyte counts. We identified a positive correlation between malnutrition score and the reduction in serum albumin and anthropometric indices (TSF and MAMC).…”
Section: Discussionmentioning
confidence: 99%
“…Each parameter was evaluated between 1 and 5 points; thus, a total malnutrition score was calculated for each case (subjective global assessment). 12 The anthropometric characteristics of the patients were recorded using standard techniques. Body weight and height were measured, and the body mass index was calculated as body weight divided by the square of the height.…”
Section: Malnutrition Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Demographic, clinical and laboratory data and the water parameters were recorded on both occasions. Nutritional evaluation was also performed using subjective global assessment (SGA) (16)(17)(18). Blood was collected from each patient before a hemodialysis session for serum albumin, CRP, interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) determination.…”
Section: Methodsmentioning
confidence: 99%